(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Series of indoline derivatives were synthesized using N-(4-aminophenyl) indoline-1-carbothiamide as a precursor. The structures of synthesized compounds were confirmed by Â Â FT-IR, 1H-NMR, 13C-NMR and LC-MS. The in vitro anti-inflammatory activity of synthesized indoline derivatives were examined by standard anti-denaturation assay. The compounds 4a (IC50 = 62.2 Âµg/ml) and 4b (IC50 = 60.7 Âµg/ml) showed potent inhibition on protein denaturation. The compounds 5a (IC50 = 97.8 Âµg/ml) exhibits moderate inhibition on protein denaturation